Anteseden pemanfaatan insentif PPh final UMKM di masa pandemi - Usman Nur Hamzah (Universitas Pamulang, 2022)
The utilization of tax incentives, especially the incentive of final income tax of MSMEs (micro, small, and medium enterprises), is still considered low from the predetermined allocation. This study aims to analyze the factors that influence the utilization of MSMEs' final income tax incentives during the covid-19 pandemic. This research was conducted by distributing questionnaires to Msmes taxpayers in the working area of KPP Pratama Probolinggo. The data analysis method uses structural equation modeling (SEM) with 147 respondents as the research sample. The results showed that taxpayers' knowledge about the MSMEs' final income tax incentives significantly affected the intention to apply the incentives. Besides that, the socialization of the MSMEs' final income tax incentives significantly affects the intention to apply the incentives through knowledge. Perceived value and financial condition do not significantly affect the intention to apply the incentives. Educational socialization about MSMEs' final income tax incentives must be carried out effectively so taxpayer knowledge can further increase the intention to take advantage of MSMEs' final tax incentives.AbstrakPemanfaatan insentif PPh final UMKM dinilai masih rendah dari alokasi yang telah ditetapkan. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi pemanfaatan insentif PPh final UMKM di masa pandemi covid-19. Penelitian ini dilakukan dengan menyebarkan kuesioner kepada Wajib Pajak UMKM di wilayah kerja KPP Pratama Probolinggo. Hasil penelitian menunjukkan bahwa pengetahuan Wajib Pajak tentang insentif PPh final UMKM berpengaruh signifikan terhadap minat pemanfaatan insentif. Sosialisasi insentif PPh final UMKM juga berpengaruh signifikan terhadap minat pemanfaatan insentif melalui pengetahuan. Selain itu, persepsi nilai dan kondisi keuangan tidak berpengaruh signifikan terhadap minat pemanfaatan insentif. Sosialisasi yang bersifat edukasi tentang insentif PPh final UMKM perlu dilakukan secara efektif sehingga terbentuk pengetahuan Wajib Pajak dan selanjutnya dapat meningkatkan minat untuk memanfaatkan insentif PPh final UMKM.